0483 Predictors of Cognitive Behavioral Therapy for Insomnia (CBT) Outcomes in Active Duty U.S. Army Personnel. (27th May 2020) - Pruiksma, K E; Hale, W; Mintz, J; Peterson, A; Young-McCaughan, S; Wilkerson, A; Nicholson, K; Dondanville, K; Fina, B; Borah, E; Roache, J; Litz, B T; et al.
Abstract: Introduction: Cognitive behavioral therapy for insomnia (CBTi) is well established as the first-line treatment for the management of chronic insomnia. Identifying predictors of response to CBTi should enable the field to efficiently utilize resources to treat those who are likely to respond and to personalize treatment approaches to optimize outcomes for those who are less likely to respond to traditional CBTi. Although a range of studies have been conducted, no clear pattern of predictors of response to CBTi has emerged. Methods: The purpose of this study was to examine the impact and relative importance of a comprehensive group of pretreatment predictors of insomnia outcomes in 99 active duty service members who received in-person CBTi in a randomized clinical trial. Results: Results indicated that higher levels of baseline insomnia severity and total sleep time predicted greater improvements on the Insomnia Severity Index (ISI) following treatment. Higher depression symptoms and a history of head injury predicted a worse response to treatment (i.e., smaller improvements on the ISI). Conclusion: Clinically meaningful improvements, as measured by the reliable change index (RCI), were found in 59% of the sample. Over and above baseline insomnia severity, only depressive symptoms predicted this outcome. Future studies should examine if modifications to CBTi based on these predictors of response can improve outcomes. Support: This study was conducted with support from the U.S. Department of Defense through the U.S. Army Medical Research and Materiel Command, Congressionally Directed Medical Research Programs, Psychological Health and Traumatic Brain Injury Research Program award W81XWH-10-1-0828 (PI: Dr Taylor).